IL12R beta 1 defect presenting with massive intra-abdominal lymphadenopathy due to Mycobacterium intracellulare infection - (:unkn) unknown (ALLERGY IMMUNOL SOC THAILAND, 2017)
Infections due to non-tuberculous mycobacteria species are problematic for immunodeficient individuals. Mendelian susceptibility to mycobacterial diseases (MSMD) defines a group of genetic defects affecting cellular interactions and the interferon (IFN)-gamma pathway. Patients with MSMD may present with a disseminated infection resulting from the Bacillus Calmette-Guerin vaccine, Mycobacterium tuberculosis complex, environmental nontuberculous mycobacteria or Salmonella species. Atypical mycobacterial infections and deficient granuloma or giant cell formation are important indicators for MSMD, especially in patients with a family history of parental consanguineous marriage. Herein we report the case of a boy with an IL-12R beta 1 defect who presented with massive intra-abdominal lymphadenopathy due to Mycobacterium intracellulare infection. The patient was born to consanguineous parents, both heterozygous for the IL-12R beta 1 defect mutation. Debulking surgery was planned in order to decrease the abdominal mass, but could not be performed due to a high risk of fatal outcomes. He has been receiving linezolid, levofloxacin, azithromycin, rifabutin and IFN-gamma therapy for the past 14 months. At follow-up, the patient showed significant clinical improvement and weight gain.
Keywords: Atypical mycobacteria; Child; Immune deficiency; Mycobacterium intracellulare; IL-12R beta 1 defect; MENDELIAN SUSCEPTIBILITY; IL-12R-BETA-1 DEFICIENCY; CLINICAL-FEATURES; DISEASE; AVIUM; TUBERCULOSIS; CHILD